2005
DOI: 10.1074/jbc.m507916200
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosylation of Human Glutathione Transferase P1-1 with Dinitrosyl Diglutathionyl Iron Complex in Vitro and in Vivo

Abstract: We have recently shown that dinitrosyl diglutathionyl iron complex, a possible in vivo nitric oxide (NO) donor, binds with extraordinary affinity to one of the active sites of human glutathione transferase (GST) P1-1 and triggers negative cooperativity in the neighboring subunit of the dimer. This strong interaction has also been observed in the human Mu, Alpha, and Theta GST classes, suggesting a common mechanism by which GSTs may act as intracellular NO carriers or scavengers. We present here the crystal str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
165
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(175 citation statements)
references
References 43 publications
10
165
0
Order By: Relevance
“…ROS and RNS have been shown to modulate intracellular iron (32). The effect of BSO also shows that the CIP-dependent nitrosative pathway is unaffected by changes in GSH or other LMW thiol ( Table 1), indicating that GSH-DNICs (33) are not obligatory intermediates, nor are other products of the interaction between GSH and the CIP.…”
Section: Discussionmentioning
confidence: 89%
“…ROS and RNS have been shown to modulate intracellular iron (32). The effect of BSO also shows that the CIP-dependent nitrosative pathway is unaffected by changes in GSH or other LMW thiol ( Table 1), indicating that GSH-DNICs (33) are not obligatory intermediates, nor are other products of the interaction between GSH and the CIP.…”
Section: Discussionmentioning
confidence: 89%
“…GST P1-1 Inhibits 59 Fe Release from Cells Hyper-expressing MRP1-Although GSTs bind DNICs (14,15), their role in iron and NO metabolism in intact mammalian cells has never been assessed, particularly in the context of their relationship with MRP1. Considering that GSTs bind DNICs (14,15), MCF7-VP cells transfected with GSTA1, GSTM1, or GSTP1 (VP␣, VP, or VP) and their relevant controls (VP Vector or VP Vector*) ( Fig.…”
Section: Mcf7-wt and Mcf7-vp Cells Stably Transfected With Gsts As Momentioning
confidence: 99%
“…Subsequently, we discovered that the glutathione (GSH) transporter, multidrug resistance protein 1 (MRP1), mediates NO-stimulated iron and GSH efflux from cells and that this process could be inhibited by L-buthionine-(S,R)-sulfoximine (BSO) (12), an inhibitor of GSH synthesis (13). Several recent investigations have suggested that DNICs such as dinitrosyl-diglutathionyl iron complexes can bind to glutathione S-transferase (GST) isoenzymes with high affinity (K d ϭ 10 Ϫ7 -10 Ϫ10 M) (14,15). In fact, a crystal structure of the DNIC-GST P1-1 complex (PDB ID: IZGN) revealed that Tyr-7 in the active site of the enzyme coordinates to iron in the DNIC, displacing one GSH ligand (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[207,208] Casini, Lo Bello et al reported on the use of several techniques including MS to study the interaction between auranofin and GST P1-1. [209] Auranofin was found to inhibit the activity of the protein in the same IC 50 values range than a known organic inhibitor (ethacrynic acid), and the molecular mechanism of inhibition was studied by ESI-FT-ICR-MS. After 30 min incubation with P1-1, adducts corresponding to [GST P1-1+Au(PEt) 3 ] and [GST P1-1+2(Au(PEt) 3 )] were detected and were found stable overtime, indicating that at least two gold binding sites are accessible.…”
Section: Glutathione-s-transferasementioning
confidence: 99%